PERAN MOTIVASI DAN KINERJA PENYULUH PERTANIAN DALAM MENGUBAH PERILAKU PETANI JAGUNG - Mohamad Ikbalbahua (Jurnal Sosial Ekonomi Pertanian, 2018)
The purpose of this study are: (1) identify the influence of competence that can improve the performance of agricultural extension in the development of maize farming, (2) examine the influence of competence and performance of agricultural extension on the behavior of corn farmers, and (3) analysis the impact of extension performance agriculture corn farmers on changing behaviors. Research conducted in Gorontalo Province in Maret until Juni 2018. The study was "ex post facto," The smallest unit of observation is the agricultural extension numbering 118 persons. Data collected through interviews using a questionnaire. Data were analyzed using LISREL 8.30 SEM program. Results showed the influence of competence on the performance of agricultural extension is influenced by the dimensions of Capacity building and needs affiliated. Variable motivation of extension agents indirect influence on corn farmers' behavior changes, while the performance of agricultural extension through the dimensions of quality of appreciation of cultural diversity and quality of management information direct impact on farmer behavior with the influence coefficient of 0.83 unit. Impact of agricultural extension agent performance impact on changing behaviors through a dimension of competence corn farmers and farmers with farmer participation coefficient of determination (R2) equal to 69 percent.